2012
DOI: 10.1097/scs.0b013e3182543231
|View full text |Cite
|
Sign up to set email alerts
|

Puncture of Foramen Ovale Cranium in Computed Tomography Three-Dimensional Reconstruction

Abstract: The study aimed to provide the anatomic data for puncture of foramen ovale cranium in oral cavity. We scan 100 volunteers' skull on computed tomography who have no lesion of skull base, of which the images were for three-dimensional reconstruction. The following observations and measurements were carried out: the shape, size of foramen ovale cranium, and the angle and length of puncture line. The results we got are the following: foramen ovale cranium appears as oval, kidney shape, round, pear shape, and strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…A few studies have addressed cannulation angles; however, most reported the angulation relative to the axial plane. 3539 Yao et al 36 measured angular relationships between the FO and TI via CT scan in a population of 120 individuals, presumably Chinese, by using the sagittal plane as a reference. Their study measured the angle between the center of the FO and boundaries of the TI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies have addressed cannulation angles; however, most reported the angulation relative to the axial plane. 3539 Yao et al 36 measured angular relationships between the FO and TI via CT scan in a population of 120 individuals, presumably Chinese, by using the sagittal plane as a reference. Their study measured the angle between the center of the FO and boundaries of the TI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the angle between the surgical tool and the axial plane has been reported to be 49.37 degrees for men and 52.26 degrees for women. 35 Huo et al 37 noted that the approach angle ranged from 38.47°–51.89° with an average of 46.09° relative to the Reid line, which deviates from the axial plane (i.e. Frankfort horizontal line or orbitomeatal line) by approximately 7° to 10°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3438 In 2013, Huo et al 36 described that “[t]he angle of introducing the cannula ranged from 15.17°–35.48° rotation to the midline with an average of 26.24° and 38.47°–51.89° angulation to the Reid line with an average of 46.09°.” In 2014, Huo et al 37 noted that “[t]he angle of introducing the cannula ranged from 15.32° to 35.48° rotation to the midline (average 25.18°) and 38.47°–51.89° angulation to the Reid line (average 46.17°).” Zhu et al 38 noted that “[t]he horizontal component of the angle between the needle axis and y axis should be more than 22 degrees in women and 20 degrees in men to avoid the injury of arteria meningea media.” Yao et al 35 noted that the angle formed by a line connecting the center of the foramen ovale with the medial edge of the trigeminal impression and the sagittal plane was an average of 6.62°. They noted that the angle formed by a line connecting the center of the foramen ovale with the lateral edge of the trigeminal impression was an average of 50.74°.…”
Section: Discussionmentioning
confidence: 99%